Goodman Ace papers - Ace, Goodman
Bound volumes containing approximately two thousand scripts and related correspondence for radio and television programs for which Ace wrote. Most of the radio scripts are for Easy Aces, a program which he wrote, produced, directed, and starred in with his wife, Jane Ace, from 1928 to 1945. Also includes radio scripts for the Danny Kaye Show and television scripts for the Milton Berle Show (1953-1955) and the Perry Como Show and Como's television specials (1961-1967).
Microfilm edition of the first volume of Easy Aces radio scripts available
Microfilm produced from originals in the Manuscript Division.
Author and radio personality. Born Goodman Aiskowitz. Born 1899; died 1982.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ace, Jane, -- 1900-1974.; Danny Kaye show (Radio program); Easy Aces (Radio program); Milton Berle show (Television program); Perry Como Show (Television program); Radio scripts; Television scripts; Television specials; Authors; Radio personalities